Probiotic Enterococcus mundtii Isolate Protects the Model Insect Tribolium castaneum against Bacillus thuringiensis - Grau, Thorben; Vilcinskas, Andreas; Joop, Gerrit (Frontiers in Microbiology, 2017)
Enterococcus mundtii strains isolated from the larval feces of the Mediterranean flour moth Ephestia kuehniella show antimicrobial activity against a broad spectrum of Gram-positive and Gram-negative bacteria. The in vitro probiotic characterization of one isolate revealed a high auto-aggregation score, a hydrophilic cell surface, tolerance for low pH, no hemolytic activity, and susceptibility to all tested antibiotics. We used the red flour beetle Tribolium castaneum, an established model organism, for the in vivo characterization of one probiotic E. mundtii isolate from E. kuehniella larvae. Tribolium castaneum larvae were fed orally with the probiotic isolate or the corresponding supernatant and then infected with either the entomopathogen Bacillus thuringiensis or Pseudomonas entomophila. Larvae exposed to the isolate or the supernatant showed increased survival following infection with B. thuringiensis but not P. entomophila. Heat treatment or treatment with proteinase K reduced the probiotic effect of the supernatant. However, the increased resistance attracts a fitness penalty manifested as a shorter lifespan and reduced fertility. T. castaneum has, pending on further research, the potential as an alternative model for the pre-screening of probiotics.